Effect of natural gas injection timing on performance and emission characteristics of marine low speed two-stroke natural gas/diesel dual-fuel engine at high load conditions. (15th April 2022) - Yu, Hongliang; Chen, Jiafeng; Duan, Shulin; Sun, Peiting; Wang, Weiwei; Tian, Haitao
Highlights: The advance of natural gas injection timing (NGIT) increased the power and thermal efficiency. The NGIT had an optimal value to reduce CH4 and NO emissions. The combustion process had two unstable periods, a stable period and a long tail heat release. Each combustion stage was affected by the NGIT in different rules. Abstract: The scavenging mode, injector position and combustion chamber type of marine low-speed two-stroke dual-fuel engines are different from those of small and medium-sized engines. The combustion process and emission laws of marine low-speed two-stroke dual-fuel engines cannot fully replicate small and medium-sized engines. The aim of this paper is to numerically investigate combustion process and emissions of marine low-speed two-stroke dual-fuel engine with different natural gas injection timings (NGIT). Four NGIT (8 BTDC, 6BTDC, 4BTDC and 2BTDC) were employed. The results showed that the advance of NGIT increased the power, thermal efficiency and NO emission, but decreased methane (CH4 ) emission. Each combustion stage was affected by the NGIT in different rules. The combustion process had two unstable periods, a stable period and a long tail heat release. The NGIT had an optimal value (6°CA BTDC ∼ 4°CA BTDC) to reduce CH4 and NO emissions. With the NGIT advanced ahead every 2°CA, the power increased by 117 kW, the thermal efficiency increased by 0.7%, the peak cylinder pressure increased by 7%, the peak high temperature volume increased by 0.8%, the peak radial flame propagation velocity increased by 3.7 m/s, the peak axial flame propagation velocity increased by 2.7 m/s, and NO emission increased by 15.4%, while the combustion interruption factor decreased by 1.18%, and CH4 emission decreased by 7.6%.